2016
DOI: 10.1530/eje-15-0673
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSIS OF ENDOCRINE DISEASE: On the need for national-, racial-, or ethnic-specific standards for the assessment of bone maturation

Abstract: In an attempt to overcome ethnic and racial differences in skeletal maturation, the use of ethnic-specific standards has been suggested. Do we need such standards? Based on a fundamental understanding of phenotypic plasticity and an individual's ability to respond to environmental cues, the author argues that we do not need ethnic-specific standards for bone maturity. I suggest that we use a unified international standard of bone maturity for comparing the health, nutrition, and quality of life of all children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…These points also highlight the need for carefully constructed, regularly updated skeletal maturation standards, along with improved understanding of the complex relationship between the myriad environmental, nutritional, anthropometric, genetic, and other factors that influence development of the pediatric skeleton. (40) In conclusion, in a non-obese, otherwise healthy cohort in the United States, we have shown that skeletal maturation is more advanced in AA children compared to non-AA children, accounting for age, body composition, and sexual maturation. This observation is novel, because previous studies have suggested that excess adiposity and earlier pubertal timing are sufficient to explain the more advanced skeletal maturation observed in AA children.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…These points also highlight the need for carefully constructed, regularly updated skeletal maturation standards, along with improved understanding of the complex relationship between the myriad environmental, nutritional, anthropometric, genetic, and other factors that influence development of the pediatric skeleton. (40) In conclusion, in a non-obese, otherwise healthy cohort in the United States, we have shown that skeletal maturation is more advanced in AA children compared to non-AA children, accounting for age, body composition, and sexual maturation. This observation is novel, because previous studies have suggested that excess adiposity and earlier pubertal timing are sufficient to explain the more advanced skeletal maturation observed in AA children.…”
Section: Discussionmentioning
confidence: 57%
“…These points also highlight the need for carefully constructed, regularly updated skeletal maturation standards, along with improved understanding of the complex relationship between the myriad environmental, nutritional, anthropometric, genetic, and other factors that influence development of the pediatric skeleton. (40) …”
Section: Discussionmentioning
confidence: 99%
“…Both GP and TW3 SAs have been labeled as the "current gold standards" for assessing skeletal maturity [99], while others refer to TW3 as the "gold standard" [102]. TW3 rather than TW2 has been recommended for use clinically [54] and as the "method of first choice" [52].…”
Section: Characteristics Of Players Who Had the Same Maturity Status mentioning
confidence: 99%
“… 29 Other authors argue that a unified international standard of bone maturity should be maintained for comparing health, nutrition, and quality of life of all children, regardless of their race, nationality, and ethnicity. 30 In this study, we selected the GP method, because it is the most popular method in Taiwan.…”
Section: Discussionmentioning
confidence: 99%